Management of Massive Pulmonary Embolism - Polaková, Eva; Veselka, Josef (International Journal of Angiology, 2022)
Pulmonary embolism is a potentially lethal manifestation of venous thromboembolic disease. It is one of the three main causes of cardiovascular morbidity and mortality in developed countries. Over the years, better diagnostic and risk stratification measures were implemented. A generous range of new treatment options is becoming available, particularly for management of massive pulmonary embolism. Nonetheless, clinicians often face uncertainty in clinical practice due to lack of scientific support for available treatment options. The aim of this article is to review management of massive pulmonary embolism.
Keywords: pulmonary embolism; massive pulmonary embolism; high-risk pulmonary embolism; reperfusion treatment; thrombolysis; embolectomy; ECMO